Locally expressed IGF1 propeptide improves mouse heart function in induced dilated cardiomyopathy by blocking myocardial fibrosis and SRF-dependent CTGF induction - Melissa Touvron; Brigitte Escoubet; Mathias Mericskay; Aude Angelini; Luciane Lamotte; Maria Paola Santini; Nadia Rosenthal; Dominique Daegelen; David Tuil; Jean-François Decaux (Disease Models & Mechanisms, 2012)
SUMMARY Cardiac fibrosis is critically involved in the adverse remodeling accompanying dilated cardiomyopathies (DCMs), which leads to cardiac dysfunction and heart failure (HF). Connective tissue growth factor (CTGF), a profibrotic cytokine, plays a key role in this deleterious process. Some beneficial effects of IGF1 on cardiomyopathy have been described, but its potential role in improving DCM is less well characterized. We investigated the consequences of expressing a cardiac-specific transgene encoding locally acting IGF1 propeptide (muscle-produced IGF1; mIGF1) on disease progression in a mouse model of DCM [cardiac-specific and inducible serum response factor (SRF) gene disruption] that mimics some forms of human DCM. Cardiac-specific mIGF1 expression substantially extended the lifespan of SRF mutant mice, markedly improved cardiac functions, and delayed both DCM and HF. These protective effects were accompanied by an overall improvement in cardiomyocyte architecture and a massive reduction of myocardial fibrosis with a concomitant amelioration of inflammation. At least some of the beneficial effects of mIGF1 transgene expression were due to mIGF1 counteracting the strong increase in CTGF expression within cardiomyocytes caused by SRF deficiency, resulting in the blockade of fibroblast proliferation and related myocardial fibrosis. These findings demonstrate that SRF plays a key role in the modulation of cardiac fibrosis through repression of cardiomyocyte CTGF expression in a paracrine fashion. They also explain how impaired SRF function observed in human HF promotes fibrosis and adverse cardiac remodeling. Locally acting mIGF1 efficiently protects the myocardium from these adverse processes, and might thus represent a therapeutic avenue to counter DCM.